Para-aortal Ganglion Mimicking a Lymph Node Metastases on 68Ga-PSMA PET/CT. (November 2020) - Schweighofer Zwink, Gregor; Rendl, Gundula; Schmeller, Nikolaus; Pirich, Christian
Abstract : Abstract: PSMA-based nuclear medicine imaging impacts increasingly the clinical decision process in prostate cancer patients. A well-known PSMA pitfall is uptake into autonomic ganglia. The intensity of uptake, the shape, and the exact location of the correlating structure in CT are supposed to aid discriminating between ganglia and lymph node metastases. In this patient, we found intense uptake in a nodular shaped para-aortal soft tissue lesion suspicious of a lymph node metastases at staging as well as restaging. After secondary resection, the lesion was histologically proven an autonomic ganglion with intense PSMA expression.